DNA Nanobiosensors: An Outlook on Signal Readout Strategies. (30th May 2017) - Chandrasekaran, Arun Richard
Abstract : A suite of functionalities and structural versatility makes DNA an apt material for biosensing applications. DNA-based biosensors are cost-effective and sensitive and have the potential to be used as point-of-care diagnostic tools. Along with robustness and biocompatibility, these sensors also provide multiple readout strategies. Depending on the functionality of DNA-based biosensors, a variety of output strategies have been reported: fluorescence- and FRET-based readout, nanoparticle-based colorimetry, spectroscopy-based techniques, electrochemical signaling, gel electrophoresis, and atomic force microscopy.